Rare phalanges soft tissue and bony metastasis in vulvar squamous cell carcinoma: Case report - Landon Foulger; Kelly Simmons; Michael Schiano; Stephen Bush, II (Elsevier, 2024)
Vulvar cancer accounts for 0.3 % of new cancer cases within the Unites States. Metastatic vulvar cancer with disease beyond the pelvis is rare and has a poor prognosis. Data on primary treatment including systemic treatments for distant metastatic vulvar disease is limited due to rarity and lack of clinical trials. The purpose of this article is to present an atypical presentation of recurrent vulvar squamous cell carcinoma with metastasis to phalanges soft tissue and bone, clavicle and to the lungs and intracranial space.